WEB ДАСТУРЛАШ ФАНИДАН МУСТАҚИЛ ТАЪЛИМНИ ТАШКИЛ ҚИЛИШДА ОНЛАЙН ТИЗИМЛАРДАН ФОЙДАЛАНИШ УСУЛЛАРИ - Атаджанов, Х. (SCIENCE and SOCIETY, 2024)
The article considers the experience of preparing web development in higher education. The training criteria are determined, aimed at the formation of a certain competence of bachelors for independent work in the field of web design or web programming. Studied online systems in the organization of independent work of students of web technologies and programming.
Keywords: self-directed learning; educational technology; Web2.0; Web3.0; case-based learning; project-based learning; electronic educational resources